Entrepreneurial reintention in pandemic. The case of Quindío (Colombia) (Revista de Investigaciones Universidad del Quindío, 2022)
The objective of this work is to analyze the sociodemographic factors that determine the reintention to create new enterprises in entrepreneurs who closed their businesses due to the COVID-19 crisis in the department of Quindío (Colombia). This research is of a correlational type, the research design is non-experimental cross-sectional. A total of 196 entrepreneurs registered in the Chamber of Commerce of Armenia and Quindío who closed their businesses during the pandemic were surveyed. The data were collected through the web page www.encuestafacil.com and were analyzed by cross tabulation and Pearson's Chi-square. The results of the completed surveys show that there is a relationship between the age of the entrepreneurs and their business reintention.
Keywords: company; entrepreneur; business; pandemic